Sociālpedagoģiskā darbība 7. - 9. klašu skolēnu savstarpējo konfliktu mazināšanā vispārizglītojošajā skolā - Blūma, Laura (Latvijas Universitāte, 2021)
Lauras Blūmas diplomdarbs “Sociālpedagoģiskās darbības 7. – 9. klašu skolēnu savstarpējo konfliktu mazināšanā vispārizglītojošajā skolā” izstrādāts Latvijas Universitātes Pedagoģijas, psiholoģijas un mākslas fakultātes Skolotāju izglītības nodaļā. Mērķis ir izzināt vispārējo konfliktu, kā arī izstrādāt un aprobēt sociālpedagoģisko programmu 7. – 9. klašu skolēnu savstarpējo konfliktu mazināšanā vispārizglītojošajā skolā. Teorētiskajā daļā autore sniedz konflikta vispārēju raksturojumu, skolēnu savstarpējo konfliktu cēloņus un skolēnu savstarpējo konfliktu mazināšanas iespējas vispārizglītojošajā skolā. Praktiskajā daļā autore veic pētījumu par skolēnu savstarpējiem konfliktiem vispārizglītojošās skolas 7. – 9. klasēs. Darba autore izstrādāja un realizēja sociālpedagoģisko programmu “Sociālpedagoģiskā darbība 7. – 9. klašu skolēnu savstarpējo konfliktu mazināšanā vispārizglītojošajā skolā”.

Diploma paper “Social Pedagogical Activities to Decrease the Mutual Conflict among Students in Forms 7 – 9 in comprehensive education establishment” developed by Laura Blūma in the University of Latvia, Faculty of Education, Psychology and Art, Department of Teacher Education. The aim of the paper is to find out about the conflict overall, as well develop and approbate social pedagogical program in forms 7 – 9 in order to decrease mutual conflict in comprehensive education establishment. In the Theoretical part the author provides general characteristics of a conflict, the main reasons for conflicts and the possibility to decrease conflict in the educational institution of general education. In the Practical part the author carries out a study about the mutual conflicts among students in forms 7 – 9 in comprehensive education establishment. A social pedagogical program “Social Pedagogical Activities to Decrease the Mutual Conflict among Students in in Forms 7 – 9 comprehensive education establishment” has been developed and implemented.
Social Pedagogical Activities to Decrease the Mutual Conflict among Students in Forms 7 – 9 in Comprehensive Education Establishment
Keywords: Pedagoģija; konflikts; savstarpējie; konflikti; skolēni; sociālpedagoģiskā